2017
DOI: 10.1111/jfpp.13461
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of queen bee larvae processed by enzymatic hydrolysis

Abstract: Queen bee larvae (QBL), by‐products of royal jelly processing, was enzymatically hydrolyzed to produce bioactive peptides. Five enzymes were firstly used to obtain hydrolysates which were evaluated for their antioxidative performances. QBL hydrolyzed by pepsin, showing the highest antioxidant resistance, were prepared and isolated by ultrafiltration using different molecular weight cutoffs of <1, 1–5, 5–10, and >10 kDa. Then, hydrolysate III (MW 1–5 kDa) with the highest activity was purified through continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…The BLPHs‐I possessed high content of hydrophobic amino acids, which may contribute to the higher superoxide scavenging activity. It was consistent with a previous study of Dong et al (2017) who demonstrated that the strong superoxide radical scavenging capabilities may be owing to hydrophobic amino acids. The sequence and amino acid composition make a lot of contributions to the antioxidant capabilities.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The BLPHs‐I possessed high content of hydrophobic amino acids, which may contribute to the higher superoxide scavenging activity. It was consistent with a previous study of Dong et al (2017) who demonstrated that the strong superoxide radical scavenging capabilities may be owing to hydrophobic amino acids. The sequence and amino acid composition make a lot of contributions to the antioxidant capabilities.…”
Section: Resultssupporting
confidence: 93%
“…The commercial enzymes are used to promote the hydrolysis of protein improve its bioactivity by converting it into peptides while retaining its nutritive value (Moure, Domínguez, & Parajó, 2006). Numerous studies over the recent years have demonstrated the antioxidant properties of hydrolyzed proteins from multiple insects species, such as weaver ant ( Oecophylla smaragdina ) (Pattarayingsakul et al, 2017), male silkmoth (Liu, Wan, Liu, Zou, & Liao, 2017), and queen bee (Dong, Dong, Liu, Lu, & Yu, 2017). However, studies on the antioxidant activity of the BLP hydrolysates (BLPHs) are rarely reported, and few antioxidant sequences of BSF have been reported before.…”
Section: Introductionmentioning
confidence: 99%
“…Queen bee larva (QBL) is an important edible insect that is harvested for use as by-product of royal jelly production [ 6 ]. In contrast to worker larva, which is fed royal jelly for the first 3 days after hatching, QBL are exclusively fed royal jelly [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the increasing rate of activity was slightly improved and was constant when the concentration of Alcalase and Flavourzyme hydrolyses was increased to 20–40 mg/ml (Klompong et al, ). In the case of queen bee larvae that had been treated using five enzymes (Trypsin, α‐Chymotrypsin, Pepsin, Papain, and Neutrase), Pepsin showed the best performance of hydrolysis, due to it having the highest antioxidant activity of DPPH (40.42%), hydroxyl (46.82%), superoxide (59.80%), 2,2‐azinobis (3‐ethylbenzothiazoline‐6‐sulfonate) (63.4%), and peroxyl (987 μM Trolox equivalent/g) (Dong, Dong, Liu, Lu, & Yu, ). The antioxidant activity could be affected by the type of protease enzyme, DH (Gibbs, Zougman, Masse, & Mulligan, ), proportion of amino acid (Yang, Yang, Li, Li, & Jiang, ), molecular weight of the peptide (Klompong et al, ), and structure of the peptide (Saito et al, ).…”
Section: Introductionmentioning
confidence: 99%